A LEGAL ANALYSIS OF THE COMMERCIALIZATION OF THE MAHAR DUE TO THE ABSENCE OF LIMITS ON THE MAHAR IN THE COMPILATION OF ISLAMIC LAW - Siti Nurheliza; Muhammad Amar Adly (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2026)
Mahar is the right of a prospective wife that must be provided by the prospective husband as a consequence of the marriage contract. The Compilation of Islamic Law regulates the obligation to provide mahr but does not stipulate either a minimum or maximum limit for the amount of mahr that may be given in a marriage. The absence of such regulation grants the parties the freedom to determine the amount and form of mahr based on mutual agreement. On the other hand, this condition has the potential to encourage the phenomenon of mahr commercialization, shifting its meaning from a symbol of respect for women to a symbol of social status and economic interests. This study aims to analyze the juridical basis for the absence of mahr limitations in the Compilation of Islamic Law and its implications for the phenomenon of mahr commercialization in society. This research employs a normative legal research method with statutory, conceptual, and comparative approaches. Data were obtained through a literature study consisting of primary, secondary, and tertiary legal materials. The findings indicate that the absence of minimum and maximum limits on mahr in the Compilation of Islamic Law is based on the principles of flexibility in Islamic law, public benefit (maslahah), and respect for the diversity of customs and socio-economic conditions within Indonesian society. However, such freedom also has the potential to give rise to the commercialization of mahr, characterized by the determination of excessively high mahr as a symbol of prestige and social status. From the perspective of maqāṣid al-sharī‘ah, such practices are inconsistent with the objectives of Islamic law, which emphasize ease, public welfare, and the protection of wealth. Therefore, strengthening religious understanding and legal education is necessary to ensure that the determination of mahr remains oriented toward the values of simplicity and ease as taught in Islam.